2020
DOI: 10.1159/000512156
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Adults in Inpatient Substance Use Treatment: A Prospective Cohort Study of Patient Characteristics and Treatment Outcomes

Abstract: <b><i>Introduction:</i></b> Compared to older adults, emerging adults treated for substance use disorders (SUDs) are more likely to have unfavorable outcomes. However, few studies have investigated the baseline characteristics and treatment outcomes of emerging adults in inpatient SUD treatment. <b><i>Aims:</i></b> This study investigated differences in demographic and clinical characteristics and treatment outcomes (relapse or treatment discontinuation) among em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Studies of general SUD treatment samples have found that higher mental distress (i.e. anxiety/depression symptoms) is associated with adverse treatment outcomes [24,[27][28][29] as was also found in the current study among the patient group without COD. The higher predictive value associated with mental distress among patients without COD may be associated with untreated anxiety/depression symptoms, and/or that health care providers are insufficiently attentive to their mental health care needs following an inpatient treatment stay.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Studies of general SUD treatment samples have found that higher mental distress (i.e. anxiety/depression symptoms) is associated with adverse treatment outcomes [24,[27][28][29] as was also found in the current study among the patient group without COD. The higher predictive value associated with mental distress among patients without COD may be associated with untreated anxiety/depression symptoms, and/or that health care providers are insufficiently attentive to their mental health care needs following an inpatient treatment stay.…”
Section: Discussionsupporting
confidence: 80%
“…Among psychological variables, both baseline motivation [24][25][26] and baseline mental distress level (i.e. symptoms of anxiety/depression) [24,[27][28][29] have been found to be associated with SUD treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, variability in impulsivity could increase the odds of both heavy drinking and alcohol-related problems [ 239 ], and a significant relationship between impaired response inhibition or impulsivity and high-risk alcohol use in nonclinical populations was demonstrated [ 240 ]. Bozkurt and colleagues [ 241 ] found that—among others—self-reported trait impulsivity predicted alcohol use severity in treatment-seeking patients [ 242 ]. There have also been epidemiological studies showing a direct association between the sensation/novelty-seeking trait and SUD, especially cocaine use disorder (CUD) [ 243 , 244 , 245 , 246 ].…”
Section: Hsd Evokes Behavioural Predictors Of Drug Of Abusementioning
confidence: 99%
“…Obtaining data from both developed and developing countries to identify changes in alcohol drinking and tobacco use during the COVID-19 pandemic, and determining the plausible risk factors associated with the shift could aid in developing informed public health strategies, specially to support the people with alcohol and tobacco dependence problems. This will also assist in managing the magnitude of the alcohol-and tobacco-related problems that may differ between high-, middle-, and low-income countries 19 . Therefore, the objectives of this study were firstly, to determine the proportion of people across several countries who reported a change in alcohol drinking and tobacco use during the COVID-19 pandemic, and secondly, to determine the factors associated with the increase in alcohol drinking and tobacco use.…”
Section: Introductionmentioning
confidence: 99%